Seasonal variation of lungworm infestation of ewes at Sidi Bouzid slaughterhouse (Central Tunisia) - Khawla Elati; Sabrine Aloui; Mokhtar Dhibi; Mourad Rekik; Mohamed Gharbi (Revue d’Elevage et de Médecine Vétérinaire des Pays Tropicaux, 2018)
Respiratory strongyloses are among the most important diseases affecting sheep reared in various farming systems in many countries. In Tunisia, farmers without any scientific background carry out the control of these parasites. A survey was performed in a slaughterhouse in Sidi Bouzid District (Central Tunisia) to assess the prevalence of sheep infestation by lungworms. The study lasted 12 months and involved 720 of the slaughtered ewes. Fecal samples from each ewe were collected and examined by Baermann’s technique. Sixty-eight samples were infested with pulmonary nematode larvae (9.4 ± 2.1%). The population was dominated by Protostrongylus rufescens (4.4 ± 1.5%), followed by Dictyocaulus filaria (2.6 ± 1.2%), Cystocaulus ocreatus and Neostrongylus linearis (1.3 ± 0.8%), and finally Muellerius capillaris (0.3 ± 0.4%), whereas mixed infestations concerned 0.4 ± 0.5% of samples. Lungworm infestation was observed in all age groups with no significant difference (p = 0.64). In addition there was no significant difference in infestation between fat-tailed Barbarine (10.8 ± 3.6%) and Queue fine de l’Ouest (Western Thin Tail) (8.5 ± 2.6%; p = 0.31) sheep breeds. The lowest prevalence was recorded in spring (6.7 ± 3.6%) and the highest in winter (11.7 ± 4.8%), but the difference between seasons was not significant (p = 0.32). This study concerning the activity dynamics of lungworms should be completed by a monitoring project to determine the economic importance of these infestations and provide a solid basis for the establishment of specific control programs against these parasites in Tunisia.